Akysis bilustris, a new species of catfish from southern Laos (Siluriformes: Akysidae) - Ng, Heok Hee (Zootaxa, 2011)
Akysis bilustris, new species, is described from the Xe Kong drainage (a subdrainage of the Mekong River) in southern Laos. It is distinguished from congeners in having a unique combination of the following characters: eye diameter 14.0– 17.5% HL, serrae on posterior margin of pectoral spine 2–3 and longer than half width of spine, pectoral fin reaching to or overlapping pelvic-fin base (length 24.5–29.3% SL), adipose-fin base length 14.3–18.3% SL, body depth at anus 11.4– 13.8% SL, caudal-peduncle length 19.6–23.4% SL, caudal-peduncle depth 6.7–9.2% SL, caudal fin emarginate, and vertebrae 30–31.